Bivalent Peptide- A nd Chelator-Containing Bioconjugates as Toolbox Components for Personalized Nanomedicine - Daeg, Jennifer; Xu, Xiaoying; Zhao, Lingzhou; Boye, Susanne; Janke, Andreas; Temme, Achim; Zhao, Jinhua; Lederer, Albena; Voit, Brigitte; Shi, Xiangyang; Appelhans, Dietmar (Biomacromolecules, 2020)
While personalized therapy bears an enormous potential in cancer therapy, the development of flexible, tailorable delivery systems remains challenging. Here, we present a "tool-kit" of various avidin-based bioconjugates (BCs) for the preparation of personalized delivery systems. Corresponding BCs were synthesized using the self-assembly of avidin with various biotinylated ligands, such as one cationic glycodendrimer for dendriplex adsorption and two functional ligands for imaging (glycodendrimers with DOTA or NOTA units) or targeting (biotinylated PEG decorated with ligands). Substituting antibodies for targeting small molecules were coupled to biotin-PEG compounds for addressing the folate receptor (FR), epidermal growth factor receptor (EGFR), and prostate-specific membrane antigen (PSMA). After successful characterization and proof of good storage and redispersion properties of BCs, cytotoxicity assays and first in vivo imaging studies with 99mTc-complexing bioconjugates provide evidence that these BCs and their avidin analogues can be used as tool-kit components in theranostic systems for personalized medicine.
CRIS-Team Scopus Importer:2022-04-14